Kesiapan Sekolah terhadap Implementasi Kurikulum Merdeka (Studi Kasus di SMPN 5 Padang Panjang) - Iman Asroa BS; Hendra Susanti; Fadriati Fadriati (Pendidikan Agama Islam STIT Palapa Nusantara, 2023)
This research is based on the existence of an independent curriculum policy proclaimed by the government which gave birth to a new paradigm in the implementation of education in Indonesia. Based on this, research was conducted with the aim of describing the readiness of SMPN 5 Padang Panjang in implementing the independent curriculum. The research question prepared is how the readiness of schools to face an independent curriculum. The research was carried out at SMPN 5 Padang Panjang on 12, 19 and 26 November 2022 by means of observation and interviews with school principals, curriculum representatives, and teacher councils. The research results were analyzed and processed in a narrative and descriptive manner. The results of the study stated that various preparations had been made at SMPN 5 Padang Panjang from various groups. Readiness is carried out not only by schools, but also by school principals, curriculum representatives, PAI teachers and other subject teachers. In general, the readiness of SMPN 5 Padang Panjang is quite mature as evidenced by the ability of SMPN 5 Padang Panjang to implement the independent curriculum at level 2 with the independent category changing.